ANALYSIS OF TEACHER'S OBSTACLES IN DISTANCE LEARNING IN CLASS IV SDN/I0I MUARA BUNGO: ANALISIS KENDALA GURU DALAM PEMBELAJARAN JARAK JAUH DI KELAS IV SDN/I0I MUARA BUNGO - Muhammad Subhan; Eka Filahanasari; eki tri oktanes ad (Journal of Vocational Education and Information Technology (JVEIT), 2022)
Learning is a core activity in an educational process. Learning is carried out in class or remotely if needed if there are obstacles to meeting in a class due to situations and conditions that are not possible. This study aims to determine the teacher's analysis in distance learning in the SDN/II Muara Bungo class for the 2020/2021 Academic Year.This research is a descriptive qualitative research type. Data collection techniques used in this study were observation, interviews, questionnaires and documents. The validity test of the data used is the source triangulation test. Qualitative data analysis with data reduction, data display and data verification. The results of this study concluded that (1) the teacher's obstacles in distance learning for the 2020/2021 academic year in the process of teaching teachers encountered obstacles in distance learning (2) in the online learning process the teacher experienced problems or obstacles in the teaching and learning process and lacked attention or support. This causes students to be less than optimal in dealing with online learning. (3) lack of direct interaction from teachers to students. This is due to online learning. Teachers can only monitor students through WhatshApp media and from teacher monitoring through online learning applications, it causes students to participate less actively in learning activities using WhatsApp